TXD612 : CAD: digital design process / College of Creative Arts - UiTM, College of Creative Arts (Universiti Teknologi MARA (UiTM), 2025)
The course offers an application and advanced use of computer aided design software for textile design process. The aim of this course is to offer new opportunities for textile designers to explore the creative options by using a computer to extend beyond the traditional methods of textile design process such as developing and presenting the ideas which has been computer generated.